Policy capacity: A conceptual framework for understanding policy competences and capabilities. Issue 3 (1st September 2015) - Wu, X; Ramesh, M; Howlett, M
Abstract: Although policy capacity is among the most fundamental concepts in public policy, there is considerable disagreement over its definition and very few systematic efforts try to operationalize and measure it. This article presents a conceptual framework for analysing and measuring policy capacity under which policy capacity refers to the competencies and capabilities important to policy-making. Competences are categorized into three general types of skills essential for policy success—analytical, operational and political—while policy capabilities are assessed at the individual, organizational and system resource levels. Policy failures often result from imbalanced attention to these nine different components of policy capacity and the conceptual framework presented in the paper provides a diagnostic tool to identify such capacity gaps. It offers critical insights into strategies able to overcome such gaps in professional behaviour, organizational and managerial activities, and the policy systems involved in policy-making.